Pengaruh Transfer Tunai Program Indonesia Pintar Dan Transfer Tunai Program Keluarga Harapan Dalam Mengatasi Kemiskinan di Provinsi Gorontalo - Lisnawaty Paje; Muhammad Amir Arham; Fitri Hadi Yulia Akib (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Lisnawaty Paje. 2024 "The Influence of the Smart Indonesia Program Cash Transfers and the Family Hope Program Cash Transfers in Overcoming Poverty in Gorontalo Province". Development Economics Study Program, Department of Economics, Faculty of Economics and Business, Gorontalo State University, With Supervisor I, Prof. Dr. Muhammad Amir Arham, M.E and Supervisor II Mrs. Fitri Hadi Yulia Akib, S.E, M.E. This research aims to determine the effect of cash transfers from the Smart Indonesia Program and the Family Hope Program on Poverty in Gorontalo Province. The data used in this research is secondary data obtained from the Central Statistics Agency and the Regional Government of Gorontalo Province for the 2018-2022 period. This research uses Panel Data Analysis using the Fixed Effect Model (FEM). The results of this research show (1) the Smart Indonesia Program Cash Transfer has a positive but not significant impact on poverty in Gorontalo Province. This is caused by inappropriate allocation and use of funds, limited beneficiary quotas so that not all underprivileged students receive assistance and there are still many individuals who have not been reached. (2) The Family Hope Program Cash Transfer has a negative but significant impact on poverty in Gorontalo Province. This is because the Family Hope Program has provided assistance to poor people to meet their basic needs, thus helping to reduce the burden of expenses they bear. As a result, many PKH participants can use their income for other purposes. In addition, the Family Hope Program has helped increase the income of poor people by providing financial assistance.